Visceral adipose tissue: the link with esophageal adenocarcinoma. (April 2014) - Massl, Renate; van Blankenstein, Mark; Jeurnink, Suzanne; Hermans, John J.; de Haan, Margriet C.; Stoker, Jaap; Koek, Marcel; Niessen, Wiro J.; Steyerberg, Ewout W.; Looman, Caspar W.; Kuipers, Ernst J.
Abstract Objective. There is strong evidence for an association between obesity and esophageal adenocarcinoma (EAC). This study investigated the association between directly measured visceral adipose tissue and the risk of EAC. Methods. In a case–control setting, we measured visceral adipose tissue in patients with EAC and healthy controls. Visceral adipose tissue was determined by abdominal CT. Exclusion criteria were uninterpretable CT scans and severe comorbidity. Controls were healthy volunteers undergoing screening CT colonography. Cross-sectional areas of visceral and subcutaneous adipose tissues were measured in cm2 at L3/L4. Values of adipose tissue of EAC patients were extrapolated to stage 0 and compared to controls. The association between visceral adipose tissue and EAC was calculated with least-squares regression, adjusted for age, sex and TNM stage. Results. We included 175 EAC patients and 251 controls. While body mass index was similar in EAC patients (26.1 kg/m2) and controls (26.2 kg/m2), visceral adipose tissue was significantly higher in EAC patients at stage 0 than in controls (276 vs. 231 cm2; p = 0.015). Regarding subcutaneous adipose tissue, there was no difference. Conclusions. Patients with EAC have significantly higher visceral adipose tissue than healthy controls. Visceral adipose tissue is a risk factor in the development of EAC and seems to be more important than obesity alone.